Malaria in Hadhramout, a southeast province of Yemen: prevalence, risk factors, knowledge, attitude and practices (KAPs) - Bamaga, O.A.A.; Mahdy, M.A.K.; Mahmud, Rohela; Lim, Yvonne Ai Lian (BMC, 2014)
Background